Laminated power inductance coil and preparation process thereof
By combining iron-nickel and ferrosilicon chromium materials in miniaturized power inductors, the problems of saturation current difference and leakage of existing inductors are solved, and a high saturation current and miniaturized power inductors are achieved.
Patent Information
- Application Number
- CN202411993332.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
Existing miniaturized power inductors have the problem of poor saturation current, and stacked products have difficulties in optimizing magnetic core design, which is prone to magnetic leakage.
The laminated power inductor coil is used, combining two soft magnetic alloy materials, iron-nickel and iron-silicon chromium, to improve insulation and prevent magnetic leakage through specific hierarchical structures and material distribution.
It realizes a miniaturized and high saturation current power inductor, avoiding the occurrence of magnetic leakage, and at the same time, the manufacturing method is simple and the performance is excellent.
Smart Images

Figure CN119811845A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high saturation power inductors, and in particular to a laminated power inductor coil and a preparation process thereof. Background Art
[0002] In recent years, due to the rapid development of information technology, electronic components made of magnetic materials have been widely used in electronics, machinery, communications, new energy and other fields due to their functional characteristics such as conversion, transmission, processing of information, and energy storage. At the same time, electronic components have put forward new requirements and challenges towards high precision, high sensitivity, miniaturization, large capacity, and fast transmission. Especially with the development of AI technology, the AI functions integrated in wearable technology require compact and efficient power solutions. The demand for miniaturized power inductors is particularly urgent. The stacking molding process has significant advantages in miniaturization, but the current miniaturized power inductors generally have poor saturation current characteristics.
[0003] The laminated products have a small space and it is difficult to optimize the core design. The iron-nickel soft magnetic material with better magnetic saturation characteristics has poor insulation. To make an inductor, it needs to be coated with insulating resin on its surface. However, the iron-nickel material coated with insulating resin contains organic materials, which will cause leakage magnetic phenomena.
[0004] Therefore, there is an urgent need to develop a miniaturized, high saturation current power inductor. Summary of the invention
[0005] In order to solve the above problems, a miniaturized, high saturation current laminated power inductor is provided. The present invention adopts the following technical solutions.
[0006] A laminated power inductor coil comprises an identification layer, a conductive coil, a first external electrode, an insulating layer, a filling layer and a second external electrode, wherein the identification layer is located on the second surface, the first external electrode is located on the first surface or extends from the first surface to the fifth surface, the second external electrode is located on the first surface or extends from the first surface to the sixth surface, and its length is consistent with the external electrode located on the first surface, the insulating layer has at least one conductor hole connecting the upper and lower conductive coils, and also comprises an introduction electrode and an extraction electrode, the introduction electrode is connected to the first external electrode, and the extraction electrode is connected to the second external electrode.
[0007] Preferably, the component also contains two soft magnetic alloy materials, iron-silicon-chromium and iron-nickel, wherein the iron-silicon-chromium material is distributed on the upper and lower sides of the conductive coil, and the iron-nickel material is distributed on the same side of the conductive coil and the conductive coil protection cover.
[0008] Preferably, the soft magnetic material FeSiCr has an iron content of 89% to 94%, a silicon content of 3% to 6%, and a Cr content of 1.5% to 6%. The iron content of the soft magnetic material FeSiCr is 45% to 55%, and the nickel content of the soft magnetic material is 45% to 55%. Preferably, the particle size D50 of the iron-nickel material is between 2 and 7 um; Preferably, the D50 of the iron-silicon-chromium material is between 1um and 3um; Preferably, the thickness of the lower protective cover of the coil component is greater than 75um and less than 150um, and the thickness of the upper protective cover is greater than or equal to 75um.
[0009] Preferably, the final density of the coil component is between 6.0 g / cm3 and 6.7 g / cm3.
[0010] Preferably, the size of the coil component is between 1.0mm*0.5mm*0.5mm and 2.0mm*1.6mm*1.0mm.
[0011] A process for preparing a laminated power inductor coil comprises the following steps: Step 1: using a conductive paste to prepare a first external electrode and a second external electrode; Step 2: Use the soft magnetic material FeNi to make a lower protective cover, and make a connection hole for connecting the external electrode on the lower protective cover fn1.
[0012] Step 3: Make an inlet electrode and an outlet electrode on the lower protective cover, and repeat steps 2 and 3 for more than 2 times until the design is met.
[0013] Step 4: Make a conductive coil and an extraction electrode on the lower protective cover on which the introduction and extraction electrodes are made; Step 5: After the conductive coil and the lead-out electrode are completed, a filling layer is made. The identifier is made of soft magnetic material FeNi, the iron content of the soft magnetic material is 45% to 55%, and the nickel content of the soft magnetic material is 45% to 55%. The filling layer uses soft magnetic material FeNi with a particle size D50 between 2 and 7 um; Step 6: Further, an insulating layer is made on the component after the filling layer is made, wherein the insulating layer is made of a soft magnetic material FeSiCr, and a via hole and a via hole for connecting the lead-out electrode are made on the insulating layer; Step 7: Make a conductive coil and lead-out electrodes on the component with the insulating layer made; Step 8: Repeat steps 5 to 7 until the design is completed; Step 9: Use the soft magnetic material FeNi to make the upper protective cover; Step 10: Making an identifier on the ni2 component on the completed upper protective cover; Step 11: The component with the completed identifier is pressed in a pressure vessel at a pressure of 550 MPa or more and a temperature of 70° C. or more.
[0014] Step 11: annealing the pressed coil component at a temperature of 500° C. to 900° C. in a nitrogen or hydrogen atmosphere, preferably at 750° C., and the annealing time is 0.5 to 3 hours.
[0015] Step 12: Further, the annealed coil component is electroplated with a nickel layer and a tin layer to finally form a coil component with welding characteristics.
[0016] Preferably, the coil component obtained in step 11 has a density of 5.9 g / cm3 to 6.7 g / cm3.
[0017] The beneficial effects of the present invention are: 1. The present invention innovatively combines iron-nickel materials and iron-silicon-chromium materials, thereby improving the poor insulation of nickel soft magnetic materials and preventing magnetic leakage.
[0018] 2. From the cross section, the uppermost part, the lowermost part and the filling part are made of FeNi material, the iron content of the soft magnetic material is 45% to 55%, and the nickel content of the soft magnetic material is 45% to 55%. The particle size D50 of the soft magnetic material FeNi used in the component tc1 is between 2 and 7 um, and the present invention can prevent magnetic leakage from occurring; 3. The manufacturing method of the present invention has the advantages of simple steps, easy implementation and excellent performance.
[0019] 4 The overall structure of the present invention is highly integrated and has the advantage of miniaturization, which can meet market demand. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A structural schematic diagram of Example 1; Figure 2 is a cross-sectional view of Example 1; Figure 3 It is an exploded view of Example 1; Figure 4 A structural schematic diagram of Example 2; Figure 5 is a cross-sectional view of Example 2; Figure 6 This is an exploded view of Example 2. DETAILED DESCRIPTION
[0021] Example 1.
[0022] A laminated power inductor includes a marking layer m, a conductive coil n, an insulating layer f, a filling layer tc, a first external electrode a1, and a second external electrode a2. The marking layer is located on the second surface 2, and the external electrodes a1 and a2 are located on the first surface 1. Each insulating layer has at least one conductor hole nk, connecting the upper and lower conductive coils n, the lead-in electrode ia is connected to the first external electrode, and the lead-out electrode oa is connected to the second external electrode. The component also contains two soft magnetic alloy materials, iron-silicon-chromium and iron-nickel, wherein the iron-silicon-chromium material is distributed on the upper and lower sides of the conductive coil, and the iron-nickel material is distributed on the same side of the conductive coil and the conductive coil protection cover. The soft magnetic material FeSiCr has an iron content of 89% to 94%, a silicon content of 3% to 6%, and a Cr content of 1.5% to 6%. The iron content of the soft magnetic material FeSiCr is 45% to 55%, and the nickel content of the soft magnetic material is 45% to 55%. The particle size D50 of the FeNi material is between 2 and 7um; the D50 of the FeSiCr material is between 1um and 3um. The thickness of the lower protective cover of the coil component is greater than 75um and less than 150um, and the thickness of the upper protective cover is greater than or equal to 75um. The final density of the coil component is between 6.0g / cm3 and 6.7g / cm3. The size of the coil component is 1.0mm*0.5mm*0.5mm.
[0023] At the same time, this embodiment also provides a manufacturing process of a laminated power inductor coil, comprising the following steps: Step 1: Use conductive paste to prepare a first external electrode a1 and a second external electrode a2. Step 2: Use soft magnetic material FeNi to make the lower protective cover fn1, with an iron content of 50% and a nickel content of 50%, and make connection holes ifn1 and ofn1 for connecting external electrodes on the lower protective cover fn1. The thickness of the lower protective cover is greater than 75um and less than 150um.
[0024] Step 3: Make the lead-in electrode ia1 and the lead-out electrode oa1 on the lower protective cover. Step 2 and step 3 can be repeated more than 2 times until the design is met.
[0025] Step 4: Make a conductive coil n1 and an extraction electrode oa2 on the lower protective cover on which the introduction and extraction electrodes are made; Step 5: After the conductive coil n1 and the lead-out electrode oa2 are completed, a filling layer tc1 is made of a soft magnetic material FeNi, wherein the iron content of the soft magnetic material is 55% and the nickel content of the soft magnetic material is 45%. The filling layer tc1 uses a soft magnetic material FeNi with a particle size D50 of 5um.
[0026] Step 6: Make an insulating layer f1 on the completed tc1 component, the insulating layer is made of soft magnetic material FeSiCr, with an iron content of 92%, a silicon content of 3.5, and a Cr content of 4.5%, and the particle size D50 of the soft magnetic material FeSiCr is 2um. A via nk1 and a via of1 for connecting the lead-out electrode are made on the insulating layer f1.
[0027] Step 7: Make the conductive coil n2 and the lead electrode oa3 on the component on which the insulating layer f1 is made.
[0028] Step 8: Repeat steps 5 to 7 until the design is completed, and a filling layer TC2 is made on the conductive coil N2 and the lead-out electrode OA3. An insulating layer F2 is made on the TC2-made part, and a via hole NK2 and a via hole OF2 for connecting the lead-out electrode are made on the insulating layer F2. A conductive coil N3 and a lead-out electrode OA4 are made on the part made with the insulating layer F2. Then, a filling layer TC3 is made on the conductive coil N3 and the lead-out electrode OA4. An insulating layer F3 is made on the TC3-made part, and a via hole NK3 and a via hole OF3 for connecting the lead-out electrode are made on the insulating layer F3. A conductive wire is made on the part made with the insulating layer F3. Make a filling layer TC4 on the conductive coil n4 and the lead-out electrode OA5, make an insulating layer F4 on the finished TC4 component, make a via hole NK4 and a via hole OF4 for connecting the lead-out electrode on the insulating layer F4, make a conductive coil N5 and a lead-out electrode OA6 on the component made with the insulating layer F4, and finally make a filling layer TC5 on the conductive coil N5 and the lead-out electrode OA6, make an insulating layer F5 on the finished TC5 component, make a via hole NK5 and a via hole OF5 for connecting the lead-out electrode on the insulating layer F5, make a conductive coil N6 on the component made with the insulating layer F5, and make a filling layer TC6.
[0029] Step 9: Use soft magnetic material FeNi to make an upper protective cover fn2, the iron content of the soft magnetic material is 45%~55%, the nickel content of the soft magnetic material is 45%~55%, the particle size D50 of the soft magnetic material FeNi is between 2~7um, and the thickness of the upper protective cover is greater than 75um.
[0030] Step 10: Make an identifier m1 on the ni2 component on the completed upper protective cover. The color of the identifier m1 should have a large contrast with the ni2 on the upper protective cover, and is preferably white.
[0031] Step 11: The finished m1 component is pressed in a pressure vessel at a pressure of 550 MPa or more and a temperature of 70°C or more to obtain a density of 6 g / cm 3Coil components.
[0032] Step 11: annealing the pressed coil component in a nitrogen or hydrogen atmosphere, preferably at a temperature of 750° C. and for 2 hours.
[0033] Step 12: Electroplating the annealed coil component with a nickel layer and a tin layer to finally form a coil component with welding characteristics.
[0034] Example 2.
[0035] A laminated power inductor coil comprises a marking layer, a conductive coil, an insulating layer, a filling layer, a first external electrode a1, and a second external electrode a2, wherein the first external electrode is located on the first surface and extends from the first surface 1 to the second surface 2, the third surface 3, the fourth surface 4, and the fifth surface 5, and the second external electrode is located on the first surface and extends from the first surface to the second surface 2, the third surface 3, the fourth surface 4, and the sixth surface 6. The insulating layer has at least one conductor hole connecting the upper and lower conductive coils, the filling layer and the conductive coil are located in the same plane, and the lead-out electrode and the lead-in electrode are not provided in this embodiment.
[0036] The rest is the same as Example 1.
[0037] Example 3.
[0038] The coil component has a size of 1.6 mm*0.8 mm*0.8 mm.
[0039] The rest is the same as Example 1.
[0040] Example 4.
[0041] The coil component has a size of 1.6 mm*0.8 mm*0.8 mm.
[0042] The rest is the same as Example 2.
[0043] Example 5.
[0044] The coil component has a size of 1.4 mm*1.2 mm*0.8 mm.
[0045] The rest is the same as Example 1.
[0046] Example 6.
[0047] The coil component has a size of 1.4 mm*1.2 mm*0.8 mm.
[0048] The rest is the same as Example 2.
[0049] The comparison case is a full-end electrode made of only iron-nickel soft magnetic alloy material.
[0050] The test results are as follows.
Claims
1. A laminated power inductor, characterized in that: It includes a marking layer, a conductive coil, a first external electrode, an insulating layer, a filling layer, and a second external electrode, wherein the marking layer is located on the second surface, and the external electrode is located on the first surface; The first external electrode is located on the first surface or extends from the first surface to the fifth surface, the second external electrode is located on the first surface or extends from the first surface to the sixth surface, and its length is consistent with the external electrode located on the first surface. There is at least one conductor hole in the insulating layer, connecting the upper and lower conductive coils, and also includes an introduction electrode and an extraction electrode. The introduction electrode is connected to the first external electrode, and the extraction electrode is connected to the second external electrode.
2. According to claim 1, a laminated power inductor coil has the feature that: the component also contains two soft magnetic alloy materials, iron-silicon-chromium and iron-nickel, wherein the iron-silicon-chromium material is distributed on the upper and lower sides of the conductive coil, and the iron-nickel material is distributed on the same side of the conductive coil and the conductive coil protective cover.
3. A laminated power inductor according to claim 2, characterized in that: the soft magnetic material FeSiCr has an iron content of 89% to 94%, a silicon content of 3% to 6%, and a Cr content of 1.5% to 6%, an iron content of 45% to 55% in the soft magnetic material iron-nickel, and a nickel content of 45% to 55% in the soft magnetic material.
4. The laminated power inductor coil according to claim 3 is characterized in that the particle size D50 of the iron-nickel material is between 2 and 7 um.
5. The laminated power inductor according to claim 4, wherein the thickness of the iron-silicon-chromium material D50 is between 1 um and 3 um.
6. A laminated power inductor according to claim 5, characterized in that: the thickness of the lower protective cover of the coil component is greater than 75um and less than 150um, and the thickness of the upper protective cover is greater than or equal to 75um.
7. The laminated power inductor according to claim 6, wherein the final density of the coil component is 6.0 g / cm 3 ~6.7g / cm 3 between.
8. A laminated power inductor according to claim 7, wherein the coil component has a size ranging from 1.0 mm*0.5 mm*0.5 mm to 2.0 mm*1.6 mm*1.0 mm.
9. A process for preparing a laminated power inductor according to any one of claims 1 to 8, wherein the process comprises the following steps: Step 1: using a conductive paste to prepare a first external electrode and a second external electrode; Step 2: Use the soft magnetic material FeNi to make a lower protective cover, and make a connection hole for connecting the external electrode on the lower protective cover fn1; Step 3: Making an inlet electrode and an outlet electrode on the lower protective cover, and repeating steps 2 and 3 for more than 2 times until the design is met; Step 4: Make a conductive coil and an extraction electrode on the lower protective cover on which the introduction and extraction electrodes are made; Step 5: After the conductive coil and the lead-out electrode component are completed, a filling layer is made. The identifier is made of a soft magnetic material FeNi, the iron content of the soft magnetic material is 45% to 55%, the nickel content of the soft magnetic material is 45% to 55%, and the particle size D50 of the soft magnetic material FeNi used in the filling layer is between 2 and 7 um; Step 6: Further, an insulating layer is made on the component after the filling layer is made, wherein the insulating layer is made of a soft magnetic material FeSiCr, and a via hole and a via hole for connecting the lead-out electrode are made on the insulating layer; Step 7: Make a conductive coil and lead-out electrodes on the component with the insulating layer made; Step 8: Repeat steps 5 to 7 until the design is completed; Step 9: Use the soft magnetic material FeNi to make the upper protective cover; Step 10: Making an identifier on the ni2 component on the completed upper protective cover; Step 11: Press the component with the identifier made thereon in a pressure vessel at a pressure of 550 MPa or more and a temperature of 70° C. or more; Step 11: annealing the pressed coil component at a temperature of 500° C. to 900° C. in a nitrogen or hydrogen atmosphere, preferably at a temperature of 750° C., and the annealing time is 0.5 to 3 hours; Step 12: Further, the annealed coil component is electroplated with a nickel layer and a tin layer to finally form a coil component with welding characteristics.
10. The process for preparing a laminated power inductor coil according to claim 9, characterized in that: The coil component obtained in step 11 has a density of 5.9 g / cm 3 ~6.7g / cm 3 .